Multiple Geminated Supernumerary Premolars: A Rare Case Report - Atul Soin; Gaurav Sharma; Gayatri Soin; Anudeep Raina; Puneet Mutneja; Archna Nagpal (Hindawi Limited, 2015)
Supernumerary teeth may be defined as any teeth or tooth substance in excess of the usual configuration of 20 deciduous and 32 permanent teeth. Gemination is defined as an attempt by a single tooth bud to divide, with a resultant formation of either a large tooth with a bifid crown or two completely divided teeth throughout the crown and root. Geminated supernumerary premolar is a rarity and the possibility of multiple occurrences is even rarer. An exhaustive review of English literature and a PubMed search conducted using the terms "gemination'' and "multiple geminated supernumerary" revealed no case of multiple geminated supernumerary premolars. We report a case of multiple geminated supernumerary premolars in a 23-year-old male.